Vschool Online Education Application - Mehdiyev, Murshud (ADA University, 2020)
Development of information and communication technologies influenced almost all sectors in the world. Internet is not only source of information; it became nearly the central part of the modern business operations. Many education sources are accessible in a digital environment to satisfy the need for learning of students (Deming et al., 2012). Moreover, the well-known universities offer several educational contents on their websites for the students who are geographically apart. Although, Education is an essential factor for the individual (Treanor, 2020), single structured approaches may not fit all individuals, and there should be different educational alternatives for the students in the school environment (Spodek, 1971). The current studies underline the importance of online learning as a more effective instructional strategy than traditional Education (Ginn & Hammond, 2012). The number of people who dropped the Education in Azerbaijan dropped significantly from 84,307 in 2010 to 3,233 in 2018 (Unesco, 2019). Therefore, it can be mentioned that one of the main purposes for lower illiteracy degree among adolescents is the higher interest in Education. Besides the preliminary and traditional Education, additional courses have high potential in the local market due to different facilities and offerings which education curriculum does not provide. Vschool is an online learning platform offers online courses for the customers on many categories, including business, entrepreneurship, art, school subjects, language, programming languages, music, software, technology and so on. The mission of the company is to create flexible, cost-effective courses for people and increase the habit of e-learning offering in the local community of Azerbaijan Republic by focusing on quality education at a lower price and creating a comfortable learning environment. The primary target customer of the business plan is the people who need to learn new skills for personal purposes or career development, students who plan to apply for a higher degree and people who want to acquire new hobbies for their leisure times. Considering that, there is no particular timing in learning (Wobbekind, 2012) the business has high potential to attract extensive customer from many age groups, especially between 15 and 55. The initial focus of the marketing plan will be mainly the customer in the capital city – Baku, Azerbaijan Republic. The purpose of the single location targeting is to acquire feedback from initial customers and improve the services and closing the gaps. After adapting the services based on user preferences, all services offered Baku will be provided for all regions of the country. The values provided by the business will be reflected in every messages or advertisement channels, public relations and content marketing by emphasizing all factor which is expected to attract the potential customer from every region of the country. Modern technology, especially social network, influences customer preferences (Kumar et al., 2013). Therefore, to attract customer, Vschool plans to implement strategies through Instagram, YouTube and Facebook social media platforms due to popularity in the local community of Azerbaijan. Additional reasons for social media marketing are affordability of advertisement and the possibility of direct contact with the customers (Thackeray, Neiger, & Keller, 2012). Primary sources of Vschool will be a website and applications for smartphones. Therefore, in order to be on the first pages of the search websites, the SEO (Search engine optimization) will be implemented as the marketing strategy of the business. The pricing strategy of the company will take into consideration that the willingness to pay of the customer requires different price offerings depending on the proposed value. Although, in initial stages, the profit from the business is not expected, the primary marketing objective is assumed to reach around 656 sales in the first year of operation. In order to achieve the break-even point, 2037 sales are an objective to surpass in the tenth month of business in the second year. After closing the first 2 year with the loss, The projections of sales for the following three years of operations are 45.513,88 AZN, 89,965.35 AZN and 142,237.63 AZN respectively. For the establishment of the business, the cost of star-up will be 30 000 AZN which will be funded by the owner of the idea and friend.
Keywords: Business; Education, Online -- Azerbaijan.; Distance education -- Azerbaijan.; Vschool -- Azerbaijan.; Education application -- Azerbaijan.